Economic driving characteristics of agricultural non-point source pollution and prevention suggestions: a case study from Shandong province in China - Zhang, Shibin; Luo, Yuzi; Zhang, Pu (Frontiers in Environmental Science, 2024)
Agricultural non-point pollution (ANSP) constraints on the development of the agricultural economy, grasp the interaction between the two, and develop targeted prevention and control policies in accordance with the evolution of different stages of the characteristic is essential. This study examines the economic characteristics of ANSP in Shandong Province to propose targeted countermeasures. Selected the time series data of Shandong Province from 2000 to 2020 to test the Environmental Kuznets Curve (EKC) characteristics between ANSP and agricultural economic growth (AEG), and the Vector Error Correction model (VECM) is used further to explore the dynamic relationship and mechanism. We validate the existence of an Inverted U-shaped EKC in Shandong Province, and the inflection points of pesticides, fertilizers, and agricultural films were reached in 2007 and 2008. The changes in pesticide loss and fertilizer loss have a positive impact on the dynamics of AEG in the short term, but there is an incremental inhibition in the long term. The dynamic effect of the impulse response diagram between the amount of agricultural film residues and AEG all shows a positive impact. The average explanatory contribution of pesticide loss, fertilizer loss, and agricultural film residue toAEG decreases by 12.14%, 7.7%, and 3%, respectively. Therefore, policy suggestions are proposed to realize the coordinated development of ANSP and economic development.